STRATEGIC ANALYSIS OF AGRICULTURAL SECTOR ENTERPRISE - KOSTENIUK, Yuliia; LAZORENKO, Oleksandra (Herald of Khmelnytskyi National University. Economic sciences, 2023)
With the development of the economy and constant changes in the external environment, it became more difficult for Ukrainian agricultural enterprises to conduct their activities, especially under the influence of two factors, namely the pandemic and the war. The Ukrainian economy, companies and population had not yet recovered from the consequences of COVID-19 when a full-scale invasion began, which forever changed the realities of both the agricultural sector and entrepreneurship. Global climate changes, international trade conditions, technological development and demographic changes were also important external factors, which created new challenges and opportunities for agricultural enterprises. In this context, there is a need to carry out their strategic analysis to determine competitiveness and develop effective development strategies. However, at the moment there is a need for a more detailed study of issues related to the analysis of internal and external factors, their interrelationship and influence on strategic decision-making in the agricultural sector. Thus, the problem that needs to be solved is the development of an integrated methodological approach for the strategic analysis of agricultural enterprises, which would take into account various aspects of their functioning and the impact of changes in the external environment. The article is devoted to a strategic analysis of the agricultural enterprise «Dekoplant». Based on the performed PEST and SWOT analyses, main threats, opportunities, strengths, and weaknesses of both the internal and external environments were identified. Among the identified threats and weaknesses are changes in trade policy conditions, national legislation, currency exchange rate fluctuations (USD and Euro), a weak development strategy, and ineffective marketing platforms. The opportunities and strengths encompass heightened quality and service level demands, high product quality, a diverse range of products, extensive experience, and a large customer base. The article highlights the significance of strategic analysis for efficient enterprise management and gaining competitive advantages. Additionally, top companies in Ukraine’s agricultural sector were investigated to determine key industry trends and competitiveness. The analytical approach enables well-founded recommendations for optimizing the strategy of the «Dekoplant» enterprise considering the identified internal and external threats.